Optimalisasi Kualitas Pendidikan Melalui Strategi Layanan Akademik di SMA Nurul Jadid - Muhammad Fadali Amar; Lukman Sholeh; Durrotul Masruroh (CV Edujavare Publishing, 2025)
This research aims to determine the Optimization of Education Quality through Academic Service Strategy at Nurul Jadid High School with a focus on learning aspects, facilities, and infrastructure. Using qualitative descriptive methods, this research reveals that SMA Nurul Jadid excels in providing academic services, especially in early and formal learning. As part of the Nurul Jadid Islamic Boarding School, Nurul Jadid High School strives to provide superior educational services by involving foreign educators and providing supporting facilities. Student academic achievement indicates the school's strong academic services, contributing to student satisfaction and performance. Teachers play a central role in the learning process, and extracurricular activities provide opportunities for the development of additional skills and social relationships. In addition, quality facilities and infrastructure contribute to a conducive learning environment. Although SMA Nurul Jadid has provided excellent academic services, there is potential for improvement, especially in increasing teacher professionalism.